Perbedaan Pengaruh Latihan Aerobik dan Interval Walking Training terhadap Kadar Gula Darah Puasa pada Individu dengan Risiko Stroke - R. Trioclarise; Ganesa Puput Dinda Kurniawan; Nina Mustikasari; Yoni Rustiana Kusumawati; Restu Arya Pambudi; Liza Laela Abida; Abiyyu Hilmy Haidar (Jurnal Terapi Wicara dan Bahasa, 2026)
Background: High fasting blood sugar levels are one of the main risk factors for stroke, especially in the elderly population. Aerobic exercise and Interval Walking Training (IWT) are physical activity interventions that can help improve glycemic control. Objectives: To determine the difference in the effect of aerobic exercise and Interval Walking Training (IWT) on fasting blood sugar levels in individuals at risk of stroke. Methods: This study used a quasi-experimental design with a pre-test and post-test approach in two treatment groups. A total of 48 respondents aged 45–70 years were divided into an aerobic exercise group and an Interval Walking Training (IWT) group. The intervention was conducted for 4 weeks with a frequency of 3 times per week. Fasting blood sugar levels were measured using Point of Care Testing (POCT). Data analysis was performed using the Wilcoxon and Mann-Whitney tests. Results: The aerobic exercise group showed a significant decrease in fasting blood sugar levels (p = 0.000), whereas the Interval Walking Training (IWT) group did not show a significant decrease (p = 0.157). The Mann-Whitney test indicated a significant difference between the two groups (p = 0.012). Conclusion: Aerobic exercise is more effective than Interval Walking Training (IWT) in reducing fasting blood sugar levels in individuals at risk of stroke. Keywords: Aerobic Exercise, Interval Walking Training, Fasting Blood Glucose, Stroke Risk.